Monohibridization with Different Media Treatments on Fruit Flies (Drosophila melanogaster) - Msy Elsa Mayori Aurora; Ika Oksi Susilawati (Universitas Mataram, 2020)
Drosophilla melanogaster is a modern experimental organism in the field of genetics because it has different phenotypic characters and looks real, easy to get, cheap (can be bred in bottles containing only fermented banana media) and has a breeding time that is not too long (2 weeks with maturation time) initial sexual ie 7 hours after exiting the pupa). This study aims to differentiate male and female fruit flies, create growth media for fruit fly culture and observe the phenotype ratio of F1 monohibrid crosses. The method used is the crossing of fruit flies by inserting male fruit flies and female fruit flies into a jam jar containing the medium using fermipan and not using fermipan. The phenotype and sex of fruit flies are formed from crossing of fruit flies. The results obtained in the form of fruit flies at most can grow on agar media and added corn flour with yeast. The medium needed by fruit flies to grow is a medium rich in protein and not much water dense. The media with corn flour is strong enough to resist thawing caused by larval activity, so that many larvae are found. Based on these conclusions, it can be continued observation of the fruit fly's politen chromosome in the next research.